2013
DOI: 10.4250/jcu.2013.21.1.18
|View full text |Cite
|
Sign up to set email alerts
|

The Comparison between the Echocardiographic Data to the Cardiac Catheterization Data on the Diagnosis, Treatment, and Follow-Up in Patients Diagnosed as Pulmonary Valve Stenosis

Abstract: BackgroundIsolated pulmonary valve stenosis (PS) makes up 6-9% of all congenital heart defects among children. The initial gold standard for diagnosis, follow-up of PS is by echocardiography. However, the most accurate diagnosis still remains to be measurement of the pressure gradient through transcatheterization. The purpose of this study is to compare the difference between the echocardiographic data to the cardiac catheterization data on the diagnosis, treatment, and follow-up in patients diagnosed as PS, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 19 publications
1
14
0
Order By: Relevance
“…Most studies investigated echocardiographic determinants of clinical course in small‐to‐moderate PS, while others proposed recommendations for follow‐up and management . Evidence of accuracy of echo Doppler gradients is derived largely from interventional series with only one study specifically designed for comparison of echocardiographic Doppler gradients with invasive gradients . There are multiple studies on critical neonatal pulmonary stenosis, which are beyond the scope of this paper.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Most studies investigated echocardiographic determinants of clinical course in small‐to‐moderate PS, while others proposed recommendations for follow‐up and management . Evidence of accuracy of echo Doppler gradients is derived largely from interventional series with only one study specifically designed for comparison of echocardiographic Doppler gradients with invasive gradients . There are multiple studies on critical neonatal pulmonary stenosis, which are beyond the scope of this paper.…”
Section: Resultsmentioning
confidence: 99%
“…The lack of standardization in the echocardiographic assessment of aortic and pulmonary valve disease in children may produce heterogeneities in the assessment of disease severity. For example, varied thresholds for transvalvular gradient have been used to define mild, moderate, or severe obstruction in aortic and pulmonary stenosis . The aim of this article was to review the literature on pediatric semilunar valvular heart disease, focusing specifically on the heterogeneity and limitations of current echocardiographic classification systems.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous publications showed a good correlation between echocardiographically derived pressure gradient estimations and subsequent cardiac catheter measurements , but there are extremely limited data for the correlation of PV measurements. Dev et al reviewed PV annulus measurements in 26 patients and found a close correlation, but correlation of measurements is to be expected and is not sufficient to recommend or abandon angiographic measurements.…”
Section: Discussionmentioning
confidence: 99%
“…Pulmonary valve stenosis is a common anomaly in patients with congenital heart defects. Quantitative assessment of the severity of pulmonary valve stenosis is mainly based on the pulmonary transvalvular pressure drop, commonly estimated by continuous‐wave Doppler and recently by magnetic resonance imaging (MRI) phase contrast flow measurements . The accuracy of noninvasive measurements of the transvalvular pressure drop has been debated .…”
mentioning
confidence: 99%